Notch Signaling in Vascular Endothelial Cells, Angiogenesis, and Tumor Progression: An Update and Prospective - Akil, Abdellah; Gutiérrez-García, Ana K.; Guenter, Rachael; Rose, J. Bart; Beck, Adam W.; Chen, Herbert; Ren, Bin (Frontiers in Cell and Developmental Biology, 2021)
The Notch signaling pathway plays an essential role in a wide variety of biological processes including cell fate determination of vascular endothelial cells and the regulation of arterial differentiation and angiogenesis. The Notch pathway is also an essential regulator of tumor growth and survival by functioning as either an oncogene or tumor suppressor in a context-dependent manner. Crosstalk between the Notch pathway and other signaling pathways is pivotal in tumor progression by promoting cancer cell growth, migration, invasion, metastasis, tumor angiogenesis, and the expansion of cancer stem-like cells. In this review, we provide an overview and update of Notch signaling in endothelial cell functions, angiogenesis, and tumor progression, particularly in the development of cancer stem cells (CSCs), as well as therapeutic resistance. We also summarize recent studies on how endothelial signaling crosstalk with the Notch pathway contributes to tumor angiogenesis and the development of CSCs, thereby providing insights into vascular biology and tumor progression.